The Use of Newmark’s Translation Methods in Translating Forman’s Novel 'I Was Here' from English into Indonesian - Shabitah, Wulan; Hartono, Rudi (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
This research is aimed to find out and describe the use of Newmark’s translation methods in translating Gayle Forman’s novel I Was Here from English into Indonesian. Qualitative approach is applied because the data of this research are in the form of words, phrases, and sentences. The data of this research are taken from Gayle Forman’s novel I Was Here and its Indonesian translation by Poppy D. Chusfani. There are 1629 dialogue sentences data taken from the novel. In this research, the researcher collects and analyzes the data through examining documents. The data are collected by marking the dialogue sentences in both novels and put them into a table of observation. In doing the analysis, the researcher compares the dialogue sentences in both novels. The analysis of the translation methods is based on Pieter Newmark’s classification of translation methods. The findings of the research show that there are seven out of eight translation methods proposed by Newmark used. They are word-for-word translation method, literal translation method, faithful translation method, semantic translation method, free translation method, idiomatic translation method, and communicative translation method. Based on the frequency of the translation method used in translating the dialogue sentences of the novel which is free translation method shows that the translator wants to make the content and language of the translated text are acceptable and understandable for the target language (Indonesian) readers. Keywords: dialogue sentences, I Was Here, novel, translation methods